Drug manufacturers practice on meeting regulatory requirements for release of drug the first batch on the market in the Republic of Serbia - Janković, Goran; Bekčić, Stana; Marinković, Valentina (Archives of Pharmacy, 2022)
The first batch is a medicinal product batch manufactured or imported after the marketing authorization issuance, for the purpose of placing on the market (approved size). Agency for Medicines and Medical Devices of Serbia (ALIMS) performs laboratory quality control in accordance with approved the specification during the drug „shelf life“ and analytical procedures during drug license issuing. Submitted to the ALIMS also: samples, certificate of analysis (CoA) for analyzed batch, reference standards with appropriate certificates and other requested documentation. Manufacturers experience indicates few necessary things:The outer packaging should contain the data approved in the formal completeness of the variation, and not the data initially approved registration document;List CoA data from the „shelf life”, not from „release“ certificate;Analysis request, CoA and Batch Release Certificate should have the same batch size;Submit the placebo and appropriate documentation for the analyzed sample;Submit an unused reference standard and evidence that the cold chain has been complied with as required;The paper quality for printing drug instructions has to be 50 g/m2 ± 2% (GMP guidelines);If additional samples are submitted at the ALIMS request, the batch size has to be corrected on the Request for Analysis, CoA and Batch Release CertificateQuantities of drug samples for laboratory control provided by the client are given on the ALIMS website. Sample size and delivery of immunological drugs (vaccines, serums, toxins, allergens, blood and plasma drugs) are not the subject of this summary.